Sistem Pembatas Pembelian BBM Menggunakan RFID (Radio Frequency Identification) dan Arduino Uno - Riky Susanto; Misbah; Surya Saputra, Pressa Perdana (SM Institute, 2024)
The dwindling availability of fuel (fuel oil) in Indonesia, Pertamina is conducting a trial run on limiting purchases of fuel. Payment transactions using a card with RFID (Radio Frequency Identification) technology are one type of non-cash transaction that can be used as an alternative payment method. In this study, we will discuss the use of RFID tags to complete purchases on BBM with a predetermined number of calculations. This tool uses Arduino Uno as its microcontroller to process data received from RFID tags and RFID readers to read the value of the fuel purchase balance, which then the buyer writes down the nominal purchase using the programmed 4x4 keypad by limiting purchases to no more than a predetermined nominal in one day. This tool uses the YF-S401 flow meter sensor to determine the volume of fuel flowing in accordance with the nominal previously inputted, the data will be displayed via a 16x2 LCD in real time using the RTC DS1307 to store month, date and time data stored in the module SD card with all data obtained in measurements.